Final answer:
The explicit formula for the nth term of the sequence is an = (n+1)n - 1/(n+1). Since the term (n+1)n grows without bound and -1/(n+1) approaches 0 as n approaches infinity, the sequence is divergent.
Step-by-step explanation:
Solution for a) Explicit Formula for an
To find an explicit formula for an, we need to see a pattern in the given sequence. Looking at the given terms:
a1 = 12 - 1/2
a2 = 23 - 1/3
a3 = 34 - 1/4
a4 = 45 - 1/5
a5 = 56 - 1/6
We can observe that each term an has the form (n+1)n - 1/(n+1). Therefore, the explicit formula for the nth term, an, is:
an = (n+1)n - 1/(n+1)
Solution for b) Convergence or Divergence
For the convergence or divergence of the sequence, we consider its behavior as n approaches infinity. The term (n+1)n grows without bound, while the term -1/(n+1) approaches 0. Hence, the sequence grows indefinitely as n becomes larger, which indicates that the sequence is divergent.